Hypomethylation of Rnase6 Promoter Enhances Proliferation and Migration of Murine Aortic Vascular Smooth Muscle Cells and Aggravates Atherosclerosis in Mice - Fang, YongPeng; Li, JinShuang; Niu, XuDong; Ma, NingShun; Zhao, Jia (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Accumulating evidence has implicated DNA methylation in the progression of atherosclerosis (AS). Rnase6 has been reported to be upregulated in AS development, but the specific regulatory mechanism remains unclear. Material/Methods: Peripheral blood and sclerotic plaque tissues from 25 AS patients were collected to detect Rnase6 expression. Methylation-specific polymerase chain reaction (MSP) was used to detected Rnase6 methylation levels in the peripheral blood of AS patients. Rnase6 expression was knocked down or DNA methyltransferase 1 (DNMT1) was overexpressed in OX-LDL-treated mouse aortic smooth muscle cells (MOVAS), and cell proliferation, migration, ROS content, and inflammatory factor secretion levels were detected. 740 Y-P, a PI3K specific agonist, was introduced to verify the effect of Rnase6 promoter hypomethylation on the PI3K/Akt signaling pathway. We knocked down Rnase6 expression in ApoE-/- mice fed with a high-fat diet to examine Rnase6 promoter methylation levels. Plaque areas and inflammatory factor secretion were examined in AS mice overexpressing DNMT1. Results: Rnase6 expression was upregulated in the peripheral blood and plaque tissues of AS patients, accompanied by decreased methylation levels of the Rnase6 promoter. Interfering with Rnase6 expression or overexpressing DNMT1 in OX-LDL stimulated MOVAS inhibited cell proliferation and migration, decreased ROS content and inflammatory factor secretion, and inhibited PI3K pathway protein expression. Rnase6 expression was decreased in the peripheral blood and plaque tissues of si-Rnase6-injected mice, and Rnase6 promoter methylation was increased. Mice overexpressing DNMT1 showed less plaque areas in the aortic root and lower secretion levels of inflammatory factors. Conclusions: Hypomethylation of the promoter of Rnase6 enhanced the proliferation and migration of OX-LDL treated MOVAS, upregulated ROS content and inflammatory factor secretion levels in the cells, and activated the PI3K/Akt signaling pathway.